IMPROVING STUDENTS’ UNDERSTANDING OF MATHEMATICAL CONCEPTS THROUGH THE REALISTIC MATHEMATICS EDUCATION MODEL ASSISTED BY SIBICA VIDEOS - Wardani, Kurnia Ully; Hilyana, F. Shoufika; Riswari, Lovika Ardana (JPSD (Jurnal Pendidikan Sekolah Dasar), 2024)
The lack of variety of learning models in the learning process and the low ability to understand mathematical concepts are the background of this research. This research aims to determine the improvement of mathematical concept comprehension skills after treating the Realistic Mathematic Education (RME) model assisted by SIBICA Video. The research method used is quantitative with the type of pre-experiment research and one group pretest-posttest design. The research place was the VA class of SD Negeri Ronggo 03, and the sample of this research was 20 students consisting of 14 boys and six girls. The data collection technique uses observation, interviews, documentation, and test questions, as many as ten description questions. The quantitative data analysis technique of the normality and hypothesis tests is an N-gain test assisted by SPSS 25 software and Microsoft Excel 2013. The research results showed that the average score of the pretest was 41.75 and the posttest was 90,875, with the results of the N-gain test obtaining an average score of 0.8588 ≥ 0.7, including the high category. Thus, it concluded that the RME model assisted by SIBICA Video can improve students’ understanding of mathematical concepts on high-number material.